The Seasonal Variation of TKR Infection Rates. Issue 5 (31st May 2017) - Parkinson, Ben; Armit, Drew; Reid, Michael; Lorimer, Michelle; Harris, Ian
Introduction: A seasonal variation in the incidence of surgical site infections has been described following a number of common surgical procedures. However in the setting of elective Total Knee Replacement (TKR), the role of environmental factors is an area of research that is currently lacking from the literature. Data recently presented from our institution demonstrates a possible trend toward higher infection rates during periods of increased temperature and humidity. The aim of this study was to investigate if seasonal and geographical factors influence the rate of TKR infection within Australia. Methods: Data from the AOA National Joint Registry for all primary TKRs performed within the last 5 years was analysed to determine the revision rates for early (<12 months) post-operative infection. The infection rates for tropical regions (Darwin, Cairns, Townsville, Mackay) were compared to the remainder of the country. A month-by-month analysis was performed to determine if there was a seasonal variation within the 2 study groups. Results: During the study period a total of 207, 540 primary TKRs were performed (6, 514 tropical vs 201, 026 non-tropical regions). Overall, the rate of revision for infection was significantly higher for the tropical regions of Australia (0.80% vs 0.39%). In non-tropical regions, there was no observed seasonal variation of infection rates. In tropical regions, there was a clear seasonal variation found, with the winter months being associated with a significantly lower rate of infection than the remainder of the year (0.37% vs 0.94%). The infection rates were not significantly different between tropical (0.37%) and non- tropical (0.38%) regions during the winter period. Conclusion: To the best of our knowledge, this is the first study to investigate and demonstrate a significant influence from seasonal variation on primary TKR infection rates. This phenomenon is evident only within tropical regions, with the periods of warmer and humid weather resulting in a significantly increased risk of primary TKR infection. These findings require further investigation and research.